The Economic War Against Cuba : A Historical and Legal Perspective on the U.S. Blockade - Lamrani, Salim (Book collections on Project MUSE., 2013)
It is impossible to fully understand Cuba today without also understanding the economic sanctions levied against it by the United States. For over fifty years, these sanctions have been upheld by every presidential administration, and at times intensified by individual presidents and acts of Congress. They are a key part of the U.S. government's ongoing campaign to undermine the Cuban Revolution, and stand in egregious violation of international law. Most importantly, the sanctions are cruelly designed for their harmful impact on the Cuban people. In this concise and sober account, Salim Lamra.